(untitled) (Eduscotech, 2022)
This study aims to determine the use of LKS in grade IV students, to determine the results of science learning in grade IV students, and to determine the effect of the use of LKS on science learning outcomes in students of SDN Kincang 1. The population in this study were students of grade IV A and IV B of SDN Kincang 1 totaling 77 people. The sample of this study was taken as many as 37 students of grade IV A using a purposive sample technique. The methods used in this study were questionnaire and documentation methods. The data analysis techniques used were descriptive statistical analysis and inferential statistical analysis. Based on the results of data analysis using descriptive statistics for the use of LKS, the average value was 79.68 with a moderate category, the lowest value was 55, and the highest value was 93. And for the science learning outcomes of grade IV students, it can be seen from the student report card scores that meet the KKM, the average value was 79.43 with a moderate category, the lowest value was 75 and the highest value was 86. The results of the inferential statistical analysis of the effect of the use of LKS on science learning outcomes found that there was an effect of the use of LKS on the science learning outcomes of SDN Kincang 1 students.